Engineering competence frameworks and topic modelling - Tigran R. Topchyan (АН Арм. ССР)
Engineering education is often presented as frameworks made up of intended competences based on product lifecycle step models. Such are the Conceiving-DesigningImplementing-Operating(CDIO) syllabus and the European e-Competence Framework (e-CF). In this article we analyze the correlation between the expert created competences implemented in these models and the job market requirement quali¯cations represented as topics extracted with probabilistic topic models.
Keywords: Mathematics